Analysis and comparison of the trends in the burden of motor neuron disease in China and worldwide from 1990 to 2021 - Yanan Fu; YuXin Wei; ZiKun Pang; Jie Yang; XinGang Sun (PLoS ONE, 2026)
Purpose This study outlines the changes in the age- and sex-specific burden of motor neuron disease (MND) in China from 1990 to 2021, focusing on the prevalence, incidence, number of disability-adjusted life years and mortality. Additionally, these trends are evaluated in comparison to the Global Burden of Disease data. Methods Public data from the Global Burden of Disease database covering the period from 1990 to 2021 were analyzed to explore the burden of motor neuron disease in China and worldwide. Trends in prevalence, incidence, disability-adjusted life years (DALYs) and mortality were examined in the analysis. The average annual percentage change was calculated using Joinpoint, and the relevant 95% confidence intervals (95% CIs) were examined to identify changes in the MND burden over time. Additionally, a thorough comparative analysis was performed to investigate the differences in the MND burden between China and other regions worldwide, considering factors such as age, sex, and time periods. Results From 1990 to 2021, the age-standardized incidence rate (ASIR) of motor neuron disease (MND) in China declined from 0.65 per 100,000 to 0.46 per 100,000, whereas the global ASIR decreased slightly from 0.81 per 100,000 to 0.77 per 100,000. In contrast, the age-standardized prevalence rate (ASPR) in China increased from 2.131 per 100,000 to 2.298 per 100,000, whereas the global ASPR decreased slightly from 3.356 per 100,000 to 3.31 per 100,000. The age-standardized mortality rate (ASMR) in China increased from 0.151 per 100,000 to 0.181 per 100,000; the global ASMR also increased from 0.38 per 100,000 to 0.46 per 100,000 during this period. Moreover, the age-standardized disability-adjusted life year (ASDR) rate in China decreased slightly from 7.995 per 100,000 to 7.672 per 100,000, whereas the global ASDR increased from 11.221 per 100,000 to 12.167 per 100,000. The average annual percentage changes (AAPCs) for the ASPR, ASIR, ASDR, and ASMR in China were −1.10%, 0.25%, 0.57%, and −0.14%, respectively. In contrast, the global AAPCs were −0.16%, −0.04%, 0.58%, and 0.26%, respectively. Age and sex played distinct roles in shaping MND burden. The ASIR of MND decreased but then increased for both sexes, remaining higher for males. Its ASPR trends differed: a slight increase in males versus an increase then decrease in females. While the ASMR was consistently higher for males, the DALYs for males started to decrease but surpassed those for females. Global MND rates have remained stable. Conclusion The prevalence, incidence, DALYs and mortality of motor neuron disease in China decreased between 1990 and 2021, suggesting a relative decrease in the total burden of MND in the country. Age influences the burden of MND, with a higher occurrence incidence in children and middle-aged individuals; the prevalence of MND is highest in the younger population, whereas MND-related mortality is the highest within the middle-aged and senior populations. Compared with females, males are more likely to be affected by MND and have a greater likelihood of death. Given the rapid population aging in China, MND is expected to remain a significant public health issue.